Donor apoptotic cell–based therapy for effective inhibition of donor‐specific memory T and B cells to promote long‐term allograft survival in allosensitized recipients. Issue 10 (19th April 2020) - Dangi, Anil; Yu, Shuangjin; Lee, Frances T.; Burnette, Melanie; Knechtle, Stuart; Kwun, Jean; Luo, Xunrong
Abstract : Allosensitization constitutes a major barrier in transplantation. Preexisting donor‐reactive memory T and B cells and preformed donor‐specific antibodies (DSAs) have all been implicated in accelerated allograft rejection in sensitized recipients. Here, we employ a sensitized murine model of islet transplantation to test strategies that promote long‐term immunosuppression‐free allograft survival. We demonstrate that donor‐specific memory T and B cells can be effectively inhibited by peritransplant infusions of donor apoptotic cells in combination with anti‐CD40L and rapamycin, and this treatment leads to significant prolongation of islet allograft survival in allosensitized recipients. We further demonstrate that late graft rejection in recipients treated with this regimen is associated with a breakthrough of B cells and their aggressive graft infiltration. Consequently, additional posttransplant B cell depletion effectively prevents late rejection and promotes permanent acceptance of islet allografts. In contrast, persistent low levels of DSAs do not seem to impair graft outcome in these recipients. We propose that B cells contribute to late rejection as antigen‐presenting cells for intragraft memory T cell expansion but not to alloantibody production and that a therapeutic strategy combining donor apoptotic cells, anti‐CD40L, and rapamycin effectively inhibits proinflammatory B cells and promotes long‐term islet allograft survival in such recipients. Abstract : In a sensitized mouse model of allogeneic islet transplantation, combination therapy based on donor apoptotic cell infusions prolongs graft survival but control of late rejection with additional B cell–specific therapies is required for indefinite graft survival.